A Reinterpretation of Invocation and Intercession of the Saints - Sullivan, Patricia A. (Theological studies, 2005)
[The intercessory role of the saints often is ignored today in favor of the saints' role as models of holiness. This can obscure the theological truth communicated profoundly in invocation and intercession, namely that Christ's work is victorious in all times and places and unites all in one eschatological communion of response to his offer of salvation. The philosophical concept of intentionality appropriated theologically can direct attention to the dynamic of nature and grace involved in invocation and intercession, for a reinterpretation of this tradition that upholds properly both a past attentiveness to the symbolic capacity of the saints and a present attentiveness to the creative function of religious acts.]